Design determinants of an effective classroom for children with hearing impairments - Fuertez, Regina Mari P.
A classroom must offer an effective learning environment to all, including those with special needs. Children with hearing impairments (CHI) belong to this category of users with special needs. In learning, normal children can flexibly use any classroom for its classroom but for children with hearing impairments (CHI), a different environment should be provided to enhance their capability to learn in other means which have special provisions. With this in mind, the researcher sought to identify design determinants of an effective learning environment which caters to the needs of children with hearing impairments (CHI). The conceptual framework of the study integrates classroom design considerations and the special school's philosophy, curriculum and issues for an effective learning environment that will be helpful to children with hearing impairments (CHI). The researcher gathered data from literature review, observations, interviews and survey. Through the purposive sampling method, a group of grade two children with hearing impairments (CHI) and two normally hearing teachers were involved in the study. The findings revealed that there is a need to cater the needs of children with hearing impairments (CHI) especially inside classrooms where formal education is given. Results showed that teachers prefer a classroom that would support their goals in educating children with hearing impairments (CHI). They encourage a classroom design that would heighten visual experience among the students and address the needs for safety and accessibility. Other critical special requirements include proper space planning, careful selection of materials and finishes and strict compliance of the Department of Education, Culture and Sports, Special Education Division's minimum requirements of classroom furniture and equipment.